Endogenous and exogenous serotonin, but not sumatriptan, ameliorate seizures and neuroinflammation in the pentylenetetrazole-induced seizure model in rats - Torun, Ibrahim Ethem; Kilinc, Yasemin Baranoglu; Kilinc, Erkan (Arquivos de Neuro-Psiquiatria, 2022)
Background: Epilepsy has neuropsychiatric comorbidities such as depression, bipolar disorder, and anxiety. Drugs that target epilepsy may also be useful for its neuropsychiatric comorbidities. Objective: To investigate the effects of serotonergic modulation on pro-inflammatory cytokines and the seizures in pentylenetetrazole (PTZ)-induced seizure model in rats. Methods: Male Wistar rats were injected intraperitoneally with serotonin, selective serotonin reuptake inhibitor fluoxetine, 5-HT1B/D receptor agonist sumatriptan, or saline 30 min prior to PTZ treatment. Behavioral seizures were assessed by the Racine's scale. Concentrations of IL-1β, IL-6, and TNF-α in serum and brain tissue were determined by ELISA. Results: Serotonin and fluoxetine, but not sumatriptan, alleviated PTZ-induced seizures by prolonging onset times of myoclonic-jerk and generalized tonic-clonic seizures. The anti-seizure effect of fluoxetine was greater than that of serotonin. Likewise, serotonin and fluoxetine, but not sumatriptan, reduced PTZ-induced increases in the levels of IL-1β and IL-6 in both serum and brain tissue. None of the administered drugs including PTZ affected TNF-α concentrations. Conclusions: Our findings suggest that endogenous and exogenous serotonin exhibits anticonvulsant effects by suppressing the neuroinflammation. It seems that 5-HT1B/D receptors do not mediate anticonvulsant and anti-neuroinflammatory effects of serotonin.
Keywords: Serotonin 5-HT1 Receptor Agonists; Fluoxetine; Seizures; Epilepsy; Inflammation